Development of novel methods of assessment in oesophageal and gastric function - Tucker, Emily C. (2015)
The objective of this thesis was to develop new methodologies to assess upper gastro-intestinal function in health and disease. Several different technologies were studied in a range of upper gastro-intestinal diseases and adapted to try and provide more meaningful insights. The thesis has three main sections.